3(-2x-1)=-12

Simple and best practice solution for 3(-2x-1)=-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-2x-1)=-12 equation:


3(-2x-1)=-12

We simplify the equation to the form, which is simple to understand
3(-2x-1)=-12

Reorder the terms in parentheses
+(-6x-3)=-12

Remove unnecessary parentheses
-6x-3=-12

We move all terms containing x to the left and all other terms to the right.
-6x=-12+3

We simplify left and right side of the equation.
-6x=-9

We divide both sides of the equation by -6 to get x.
x=1.5

See similar equations:

| 8t=-122 | | -10(-8+0)-8x= | | 6(p+4)=-3(1-3p) | | 4(t+7.50)=40 | | 4x+44(2x+16)=180 | | -6+14x-10=14 | | 0.5x+0.1(x+20)=3.2 | | 2w-7w=15 | | (x+9)=20 | | x(250-2x)=0 | | -5+2(1+8v)=29 | | x(250-2x)=7200 | | 7r+(-3)=2r+72 | | 3x^3-5x^2-2=0 | | -22=-4d-5d | | 2(x-3)=1/4(8x-24) | | 10y=15 | | 8b+45c(6+-2)=68 | | 7t+(-3)=2r+72 | | -24+8-7w=15 | | 6-x=11 | | 9(2-7a)=-16 | | 7v-7v=-4(v-7)+4(1-v) | | T(x)=x^3-5x^2+4x | | 4.1b=20.5 | | 16.8-z=6v | | -2(4c-2)= | | -24+8=m-6 | | 92=-2a-6(a-6) | | 6x+3y=-13+5x+2y | | 8(3x-2y)+4[(-3)+4y]= | | -28+2n=6(n-6) |

Equations solver categories